Near-Death-Like Experiences without Life-Threatening Conditions or Brain Disorders: A Hypothesis from a Case Report - Facco, Enrico; Agrillo, Christian (Frontiers in Psychology, 2012)
Near-death experiences (NDEs) are profound psychic experiences commonly occurring in life-threatening conditions. They include feeling a sense of peace, of seeing a bright light, encountering deceased relatives or religious figures, and of transcending space and time. To explain them, it has been suggested that they stem from brain disorders and/or psychological reactions to approaching death, a sort of wishful thinking in response to the perceived threat. This is a report on a case with most of the features typical of NDEs except that it occurred entirely without any life-threatening conditions. This evidence is theoretically incompatible with either of the above hypotheses, suggesting that a broader interpretation of the phenomenon is needed.